The introduction of Bismarck's social security system and its effects on marriage and fertility in Prussia - Timothy Guinnane; Jochen Streb (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Economists have long argued that introducing social insurance will reduce fertility. The hypothesis relies on standard models: if children are desirable in part because they provide security in case of disability or old age, then State programs that provide insurance against these events should induce couples to substitute away from children in the allocation of wealth. We test this claim using the introduction of social insurance in Germany in the period 1881-1910. Bismarck's social-insurance scheme had three pillars: health insurance, workplace accident insurance, and an old age pension. Earlier studies typically focus on the pension alone; we consider all three pillars. We find that Bismarck's social insurance system affected fertility overall only via its effects on the incentive to marry. The old age insurance by itself tended to reduce marriages, but the health and accident-insurance components had the opposite effect. For people exposed to all three pillars of social insurance, the two effects cancelled each other and the aggregate effect on fertility was muted. – – Ökonomen argumentieren seit langem, dass die Einführung einer Sozialversicherung die Geburtenrate senkt. Die Hypothese stützt sich auf Standardmodelle: Wenn Kinder zum Teil deshalb wünschenswert sind, weil sie Sicherheit im Falle von Invalidität oder Alter bieten, dann sollten staatliche Programme, die eine Versicherung gegen diese Ereignisse bieten, Paare dazu veranlassen, bei der Allokation des Vermögens von Kindern abzusehen. Wir testen diese Behauptung anhand der Einführung der Sozialversicherung in Deutschland im Zeitraum von 1881 bis 1910. Bismarcks Sozialversicherungssystem hatte drei Säulen: Krankenversicherung, Arbeitsunfallversicherung und eine Altersrente. Frühere Studien konzentrieren sich typischerweise nur auf die Rente; wir betrachten alle drei Säulen. Wir finden, dass Bismarcks Sozialversicherungssystem die Fertilität insgesamt nur über seine Auswirkungen auf den Anreiz zur Heirat beeinflusste. Die Altersversicherung allein reduzierte tendenziell die Eheschließungen, aber die Kranken- und Unfallversicherungskomponenten hatten den gegenteiligen Effekt. Bei Personen, die allen drei Säulen der Sozialversicherung ausgesetzt waren, hoben sich die beiden Effekte gegenseitig auf und der Gesamteffekt auf die Fertilität war schwächer.
Keywords: H55; I13; J11; N13; N33; N43; 330; Social insurance; pensions; fertility transition; marriage; Bismarck; Prussia